Airborne Particulate Matter–Bound Heavy Metals in Sub-Saharan Africa: A Systematic Review of Sources, Exposure Pathways, and Public Health Risk Assessment - Idirisu, Jibril Limangba (Journal of Science Research and Reviews, 2026)
Particulate matter in air (PM2.5/PM10) is a major environmental problem throughout Sub-Saharan Africa (SSA), where the inherent toxicity of this pollutant relies heavily on the presence of associated heavy metals. Using this systematic review that aggregates evidence from 96 studies, the primary sources, atmospheric processing, routes of human exposure and health risk of heavy metals (Pb, Cd, Cr, Ni and As) bound to PM across the SSA are systematically assessed. The dominant sources derived from framework-based analysis include the combustion of fuels from a depreciating vehicle fleets, open burning of solid wastes including e-waste, biomass combustion from cooking activities, artisanal and industrial activities such as mining, and seasonal influx of dust from Saharan storms contributing to a regional blend of PM sources. Further, atmospheric ageing processes combined with acid-driven processing in tropical condition render heavy metals more soluble and bioavailable, thus increasing the toxicity. The main route of human exposure is inhalation while ingestion of resuspended dust significantly contributes to the risks encountered by children. Reported human health risk assessments mostly result in Hazard Index (HI) values >1.0 and Incremental Lifetime Cancer Risk (ILCR) values >10 -6 (mainly concerning Cr and Ni in urban and industrial areas), which are above acceptable thresholds of human health risk. However, the legislative framework for metallic PM in SSA is scattered, and many African nations do not have specific limits on PM bound metallic content. The absence of long-term monitoring data and limited development of regional specific source profiles are among the key gaps of knowledge. Addressing these requires harmonized air quality standards, adopted component specific regulatory mechanisms, and green chemistry based pathway development for the industrial sector in SSA.
Keywords: Sub-Saharan Africa; Particulate matter; Heavy metals; Source apportionment; Health risk assessment; Bioavailability.